2020
DOI: 10.1021/acschembio.0c00685
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity-Based Screening for Citrulline-Containing Natural Products Reveals a Family of Bacterial Peptidyl Arginine Deiminases

Abstract: Ribosomally synthesized and post-translationally modified peptides (RiPPs) are a family of natural products defined by a genetically encoded precursor peptide that is processed by associated biosynthetic enzymes to form the mature product. Lasso peptides are a class of RiPP defined by an isopeptide linkage between the N-terminal amine and an internal Asp/Glu residue with the C-terminal sequence threaded through the macrocycle. This unique lariat topology, which typically provides considerable stability toward … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 62 publications
1
18
0
1
Order By: Relevance
“…Interestingly, two distinct Streptomyces species (S. avermitilis and S. torulosus) were found to produce citrulassin variants with identical core peptide sequences, but with the citrulline modification absent in one and present in the other. Comparison of genomic sequences enabled the identification of a potentially responsible peptidylarginine deiminase (PAD), which, unlike other lasso peptide-tailoring enzymes, is not encoded locally in the lasso peptide gene cluster (Harris et al, 2020). In vivo complementation experiments confirmed the participation of the PAD (WP_064069847.1) in the biosynthesis of deiminated lasso peptides (Figure 6A).…”
Section: Peptidyl Arginine Deiminase As a Tailoring Enzymementioning
confidence: 97%
See 1 more Smart Citation
“…Interestingly, two distinct Streptomyces species (S. avermitilis and S. torulosus) were found to produce citrulassin variants with identical core peptide sequences, but with the citrulline modification absent in one and present in the other. Comparison of genomic sequences enabled the identification of a potentially responsible peptidylarginine deiminase (PAD), which, unlike other lasso peptide-tailoring enzymes, is not encoded locally in the lasso peptide gene cluster (Harris et al, 2020). In vivo complementation experiments confirmed the participation of the PAD (WP_064069847.1) in the biosynthesis of deiminated lasso peptides (Figure 6A).…”
Section: Peptidyl Arginine Deiminase As a Tailoring Enzymementioning
confidence: 97%
“…Nuclear magnetic resonance (NMR) and tandem mass spectrometry (MS/MS) analyses revealed that Arg9 of the lasso peptide was converted to citrulline. To determine the identity of the enzyme responsible for Arg deimination, researchers performed reactivity-based screening with a selective probe for citrulline-containing natural products, leading to the discovery of 13 citrulassin variants (Harris et al, 2020). Interestingly, two distinct Streptomyces species (S. avermitilis and S. torulosus) were found to produce citrulassin variants with identical core peptide sequences, but with the citrulline modification absent in one and present in the other.…”
Section: Peptidyl Arginine Deiminase As a Tailoring Enzymementioning
confidence: 99%
“…Beyond the minimal BGC required for lasso peptide biosynthesis and commonly associated transporters and isopeptidases, genome mining of the ever-growing database of bacterial genome sequences has revealed tailoring enzymes that subject lasso peptides to further post-translational modifications (PTMs). Modifications that have been confirmed experimentally include disulfide bonds, , C-terminal methylation, , acetylation, citrullination, phosphorylation, glycosylation, epimerization, , and β-hydroxylation. , All previously described lasso peptide PTMs occur in either the loop or tail regions of the lasso peptide, and these auxiliary enzymes recognize the linear precursor rather than the matured lasso as a substrate. , …”
Section: Introductionmentioning
confidence: 94%
“…3,17,24,25 Beyond the minimal BGC required for lasso peptide biosynthesis and commonly associated transporters and isopeptidases, genome mining of the ever-growing database of bacterial genome sequences has revealed tailoring enzymes that subject lasso peptides to further post-translational modifications (PTMs). Modifications that have been confirmed experimentally include disulfide bonds, 26,27 C-terminal methylation, 19,28 acetylation, 29 citrullination, 30 phosphorylation, 31 glycosylation, 32 epimerization, 26,33 and -hydroxylation. 6,34 All previously described lasso peptide PTMs occur in either the loop or tail regions of the lasso peptide, and these auxiliary enzymes recognize the linear precursor rather than the matured lasso as a substrate.…”
mentioning
confidence: 93%